Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-1015
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Domain Classification of Drowsiness in Speech: The Case of Alcohol Intoxication and Sleep Deprivation

Abstract: In this work, we study the drowsy state of a speaker, induced by alcohol intoxication or sleep deprivation. In particular, we investigate the coherence between the two pivotal causes of drowsiness, as featured in the Intoxication and Sleepiness tasks of the INTERSPEECH Speaker State Challenge. In this way, we aim to exploit the interrelations between these different, yet highly correlated speaker states, which need to be reliably recognised in safety and security critical environments. To this end, we perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Importantly, it has been shown that, where MT-SHL suffers a performance drop, incorporating task correlations helps mitigate the effects of negative transfer. Thus, our findings corroborate the importance of task relatedness for inductive transfer learning, dovetailing with previous work [7,8,9]. For example, in prior work [8], it was hypothesized that sleepiness and alcohol intoxication are related, yet, transfer learning did not improve the performance.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Importantly, it has been shown that, where MT-SHL suffers a performance drop, incorporating task correlations helps mitigate the effects of negative transfer. Thus, our findings corroborate the importance of task relatedness for inductive transfer learning, dovetailing with previous work [7,8,9]. For example, in prior work [8], it was hypothesized that sleepiness and alcohol intoxication are related, yet, transfer learning did not improve the performance.…”
Section: Resultssupporting
confidence: 90%
“…This demonstrates that our notion of task relatedness abstracts away from pure acoustic similarity, so is not simply a function of recording conditions within a dataset. Moreover, the tasks of sleepiness and intoxication are located far away from each other, indicating their dissimilarity that was also found in the work [8]. This pattern is also reflected in Fig.…”
Section: Visualizationssupporting
confidence: 67%
See 1 more Smart Citation
“…The KSS being a semi-continuous measure, the choice is made to split the dataset into two classes: following [4], [6], [9], [15], the samples with a mean KSS>7.5 will be considered as Sleepy Language (SL). On the contrary, the samples with a KSS≤7.5 are labelled as Non Sleepy Language (NSL).…”
Section: Ground Truth: the Karolinska Sleeping Scalementioning
confidence: 99%
“…Since then, there have been only few reported research on the subject [2]. The best performing automatic classification approach is still a system proposed in 2011 [3] and shares the same feature set as most research [4]- [6] computed with openSmile [7]. While some have tried to suggest using different features [8], [9], the common drawback to all of these systems is the lack of possible physiological interpretation of the features due to feature combination techniques.…”
mentioning
confidence: 99%